The spectator as a spiritual conservator of artistic heritage. Roger Marijnissen on museum education - Willem Elias (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Throughout his life Marijnissen  has often advocated the significance art education as an important aspect of a museum’s mission. He even provided some valid suggestions as to how the public can be enticed to engage more closely with a museum. In this article we get an insight into Marijnissen’s views on museum education and his answers to the question:  how to safeguard the museum collection in the minds of humanity?